2014
DOI: 10.1080/10807039.2013.805957
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health in Environmental Justice Communities: Examining Cumulative Risk in Terms of Environmental Exposures and Social Determinants of Health

Abstract: Residents of environmental justice (EJ) communities may bear a disproportionate burden of environmental health risk, and often face additional burdens from social determinants of health. Accounting for cumulative risk should include measures of risk from both environmental sources and social determinants. This study sought to better understand cumulative health risk from both social and environmental sources in a disadvantaged community in Texas. Key outcomes were determining what data are currently available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Inequality metrics for health risks are driven, in addition to exposures, by the variability in baseline health risks, demographic variables, income, and other characteristics that influence vulnerability or susceptibility. This differs from many or possibly most earlier EJ and cumulative impact analyses that have relied on exposure indicators for a showing of disproportionate impacts, e.g., using ambient monitoring and dispersion modeling (e.g., [ 6 , 7 , 8 , 73 , 74 , 75 , 76 ]), and surrogates such as proximity to traffic or point sources [ 77 , 78 ]. In addition, data from national datasets like the National Air Toxics Assessment [ 79 ] and air quality monitoring networks may not have the needed spatial resolution for local scale analyses of industry and traffic pollutants [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 95%
“…Inequality metrics for health risks are driven, in addition to exposures, by the variability in baseline health risks, demographic variables, income, and other characteristics that influence vulnerability or susceptibility. This differs from many or possibly most earlier EJ and cumulative impact analyses that have relied on exposure indicators for a showing of disproportionate impacts, e.g., using ambient monitoring and dispersion modeling (e.g., [ 6 , 7 , 8 , 73 , 74 , 75 , 76 ]), and surrogates such as proximity to traffic or point sources [ 77 , 78 ]. In addition, data from national datasets like the National Air Toxics Assessment [ 79 ] and air quality monitoring networks may not have the needed spatial resolution for local scale analyses of industry and traffic pollutants [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 95%
“…While statistical adjustment for conventional vascular risk factors partially accounts for the effects of general health on brain health, there are other known and unknown variables that may further account for this association. Multiple studies have reported epigenetic associations for multiple socioeconomic factors, [ 50 - 52 ], poorer quality diet, aspects of environment that influence opportunities for and appeal of physical activity [ 53 ] and exposure to pollution and other toxins [ 54 ]. Socioeconomic status and childhood intelligence may also contribute to lifestyle choices impacting brain vascular health [ 55 ] – intelligence and greater educational attainment were associated with health-promoting behaviours [ 56 ] and earlier adoption of health-related recommendations [ 57 ] - and exposure or tolerance to allostatic load [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such urban neighborhoods typically have relatively high burdens of environmental deterioration that includes water and other infrastructure systems, public problems such as crime and physical blight, poor public education systems, and a limited tax base. A continued focus on environmental justice communities and the cumulative risks faced by their residents is critical to protecting these residents and, ultimately, move towards a more equitable distribution and acceptable level of risk throughout society (Prochaska et al, 2014). …”
Section: Environmental Justice and Sustainable Infrastructurementioning
confidence: 99%